MODIFIED BIPHASIC MEDIA FOR BLOOD CULTURE - Devaraj, Bhuvaneshwar; Kali, Arunava; Charles M.v., Pravin; Seetha, Kunigal S (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: To evaluate the performance characteristics of Nutrient agar and MacConkey's agar biphasic medium (BPM) with conventional blood culture. Methods: We prepared two modified biphasic blood culture medium with Nutrient agar (with 1% lactose and 0.004% neutral red) and MacConkey's agar. A total of 20 standard clinical strains of bacterial pathogens and Candida albicans were inoculated in duplicate in Nutrient agar BPM, MacConkey's agar, and brain heart infusion broth to evaluate the turn-around time and performance characteristics. Results: All isolates except Streptococcus pyogenes and Streptococcus pneumoniae showed characteristic lactose fermenter and non-lactose fermenter colonies on Nutrient agar and MacConkey's agar BPM within 24 hrs with sufficient growth to carry out biochemical identification and antibiotic susceptibility testing. This resulted in a shorter turn-around time (48 hrs) when compared to that of conventional blood culture (72 hrs). Conclusion: Nutrient agar and MacConkey's agar based modified BPM could be beneficial in reducing the turn-around time of blood culture. Keywords: Biphasic media, Bloodstream infection, Conventional blood culture.